2021
DOI: 10.1038/s41388-021-01974-4
|View full text |Cite
|
Sign up to set email alerts
|

Selective inhibition of HDAC6 regulates expression of the oncogenic driver EWSR1-FLI1 through the EWSR1 promoter in Ewing sarcoma

Abstract: Ewing sarcoma (EWS) is an aggressive bone and soft tissue tumor of children and young adults in which the principal driver is a fusion gene, EWSR1-FLI1. Although the essential role of EWSR1-FLI1 protein in the regulation of oncogenesis, survival, and tumor progression processes has been described in-depth, little is known about the regulation of chimeric fusion-gene expression. Here, we demonstrate that the active nuclear HDAC6 in EWS modulates the acetylation status of specificity protein 1 (SP1), consequentl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…HDAC6 is widely expressed across tissues in the body 38 . In cancer, HDAC6 is overexpressed and known to correlate with poor prognosis 99 , 100 . Here, we observed that HDAC6 expression is increased in mdx mice, which indicates that it could participate in the DMD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 is widely expressed across tissues in the body 38 . In cancer, HDAC6 is overexpressed and known to correlate with poor prognosis 99 , 100 . Here, we observed that HDAC6 expression is increased in mdx mice, which indicates that it could participate in the DMD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC6 was reported to increase the level of the Ewing sarcoma breakpoint region 1 fusion gene (EWSR1-FLI1) [ 21 ]. A high level of HDAC6 can predict low survival of patients with Ewing Sarcoma [ 21 ].…”
Section: Mechanism Of Hdac6-promoted Cancer Cell Proliferationmentioning
confidence: 99%
“…HDAC6 was reported to increase the level of the Ewing sarcoma breakpoint region 1 fusion gene (EWSR1-FLI1) [ 21 ]. A high level of HDAC6 can predict low survival of patients with Ewing Sarcoma [ 21 ]. HDAC6 was shown to promote the invasion and migration of rhabdomyosarcoma (RMS) cells via RAC1, a Rho family GTPase [ 22 ].…”
Section: Mechanism Of Hdac6-promoted Cancer Cell Proliferationmentioning
confidence: 99%
“…A screening of 43 epigenetic drugs revealed that the most sensitive agents in EWS cell lines were related to HDAC inhibition, being BML-281, a specific inhibitor of HDAC6, the drug with the lower IC50. BML-281 increased acetylation levels of specificity protein 1 (SP1), reducing its binding to the EWSR1-FLI1 promoter and causing repression of the oncogene and its associated targets [ 48 ]. Furthermore, the combination of the HDAC6 inhibitor ACY-1215 with doxorubicin reduced tumor growth in EWS xenografts [ 48 ].…”
Section: Epigenetic and Immunotherapy-based Treatments In Ews: Moving...mentioning
confidence: 99%
“…BML-281 increased acetylation levels of specificity protein 1 (SP1), reducing its binding to the EWSR1-FLI1 promoter and causing repression of the oncogene and its associated targets [ 48 ]. Furthermore, the combination of the HDAC6 inhibitor ACY-1215 with doxorubicin reduced tumor growth in EWS xenografts [ 48 ]. On the other hand, HDAC1 and HDAC2 knockouts demonstrated a reduction in invasiveness and tumor growth in xenografts [ 49 ].…”
Section: Epigenetic and Immunotherapy-based Treatments In Ews: Moving...mentioning
confidence: 99%